PENERAPAN MODEL DISCOVERY LEARNING MENGGUNAKAN APLIKASI GEOGEBRA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI BANGUN RUANG SISI DATAR - Snae, Sesti Lestiani; Samo, Damianus Dao; Blegur, Irna Karlina Sensiana (Program Studi Pendidikan Matematika, 2025)
This research was motivated by the critical thinking ability of class VIII students at SMP Negeri 5 Kupang regarding the building materials used in flat-sided spaces, which are still low. This study describes the application of the discovery learning model using the Geogebra application to enhance the critical thinking skills of class VIII students at SMP Negeri 5 Kupang about the building materials of flat-sided spaces. The research method used is Classroom Action Research, with qualitative and quantitative data types. This research was carried out in class VIII SMP Negeri 5 Kupang, totaling 24 students. Data collection techniques in this research were through observation, tests and questionnaires, with the instruments used being teacher and student observation sheets, test questions and student response questionnaires. Implementation of this Classroom Action Research has 4 stages, namely 1) Planning; 2) Implementation of action (action); 3) Observation; 4) Reflection. The research results showed that the percentage of completeness of the results of students' classical critical thinking ability test at the end of cycle I reached 20.83%, increasing to 87.50% at the end of cycle II. The implementation of teacher teaching activity score data at the end of cycle I reached 92.50%, increasing to 98.30% at the end of cycle II and was in the very good category. In addition, the implementation of student learning activity score data at the end of cycle I reached 73.95% and also increased to 93.22% at the end of cycle II and was in the very good category.